Pemberdayaan Keterampilan Abad 21 (Literasi Digital Dan Problem Solving) Untuk Meningkatkan Daya Saing Pemuda Perum Regency Puteran - Bambang Kurnia Nugraha; Ridwan Hakiki (CV. SINAR HOWUHOWU, 2026)
The challenges of the digital era require the younger generation to possess competencies that extend beyond formal academic qualifications, particularly 21st-Century Skills rooted in digital literacy and problem-solving capabilities. Youth in PerumRegency Puteran demonstrate significant potential but still face obstacles in optimizing digital devices for productivity and applying systematic methods to resolve work or business hurdles. This Community Service (PkM) activity aims to empower the youth of PerumRegency Puteran by enhancing their digital literacy and problem-solving skills to boost their competitiveness in both the job market and the entrepreneurial sector. The program implementation utilizes the Asset-Based Community Development (ABCD) approach, which focuses on leveraging local potential through three main phases: preparation (coordination and needs assessment), implementation (interactive training, workshops, and case study mentoring), and evaluation (measuring impact through pre-tests and post-tests). The expected outcomes of this activity include an increase in digital literacy comprehension, the adoption of critical thinking frameworks (design thinking) in problem-solving, and the formation of an independent digital youth community within the residential area.